Participatory Research and Gender Analysis in Agricultural and Natural Resource Management Research - Averill, D; Lilja, Nina; Manners, G (CGIAR System Organization, 2006)
This selected bibliography provides a snapshot of reported research in participatory research and gender analysis, and as a prototype for an ongoing resource for researchers.